Joint Rail 2005
DOI: 10.1115/rtd2005-70045
|View full text |Cite
|
Sign up to set email alerts
|

Preparations for a Train-to-Train Impact Test of Crash-Energy Management Passenger Rail Equipment

Abstract: Preparations are ongoing for a full-scale train-to-train impact test of crash-energy management (CEM) equipment, during which a cab car-led passenger consist, initially moving at 30 mph, will impact a standing locomotive-led consist. The colliding consists will be of approximately equal masses. This test is planned for November 2005.The purpose of the full-scale testing program is to define the crashworthiness performance of conventional and CEM passenger equipment. In the train-to-train test of conventional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Though started relatively late, the research programme developed fast and led to several full-scale impact tests of both a single vehicle and of two coupled vehicles with a rigid wall type obstacle (termed stonewall), in the period 1999 to 2004 [7]. A train-to-train impact test was conducted later, at the end of 2005 [8]. Research for rail equipment crashworthiness was carried out [9] and a crashworthiness standard for rail vehicles running at speeds of 200 km/h and above was also issued in 1999 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Though started relatively late, the research programme developed fast and led to several full-scale impact tests of both a single vehicle and of two coupled vehicles with a rigid wall type obstacle (termed stonewall), in the period 1999 to 2004 [7]. A train-to-train impact test was conducted later, at the end of 2005 [8]. Research for rail equipment crashworthiness was carried out [9] and a crashworthiness standard for rail vehicles running at speeds of 200 km/h and above was also issued in 1999 [10].…”
Section: Introductionmentioning
confidence: 99%
“…The third curve shows the SIV associated with the predicted acceleration of the cab car in the CEM train-to-train full-scale test [16]. The final curve, for sake of reference, is the SIV associated with the acceleration measured from the lead car of the CEM two-car full-scale test [4].…”
Section: Analyze the Problemmentioning
confidence: 99%
“…The remaining two workstation tables will be included on the CEM train-to-train full-scale impact test. Two experiments are currently planned, one using the THOR ATD and one using the Hybrid 3RS ATD [16]. The objective of these experiments is to demonstrate the crashworthiness performance of the improved workstation table.…”
Section: Future Workmentioning
confidence: 99%
“…A pre-test collision dynamics model of the CEM train-totrain impact test [5] indicated that the modified force-crush behavior of the cars would result in a more severe crash pulse than in the train-to-train conventional impact test. In a train-totrain collision with conventional cars, the cab car environment will be less severe than a similar collision involving CEM equipment.…”
Section: Description Of Occupant Environmentmentioning
confidence: 99%
“…A pre-test MADYMO [9] computer model was used to simulate the occupant response for each table experiment using the predicted crash pulse from the pre-test collision dynamics model [5]. All of the predicted measurements were below the maximum acceptable injury criteria values presented in Table 4.…”
Section: Figure 14 Pre-test Photo Ofmentioning
confidence: 99%